The Effectiveness of English Language Learning Programs at a Business School: Stakeholders’ Perspectives - Donny Fahsani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to see how stakeholders perceive the English learning program at a business school in West Java, Indonesia. Looking at the aspects of learning needs, curriculum quality, and students' English proficiency; this research is part of the English curriculum design at the institution. This study used a mixed method. The questionnaires were distributed to various stakeholders. The sampling was carried out in a stratified non-random manner. A total of 90 student questionnaires, eight questionnaires from senior lecturers of subject matter, five questionnaires from English lecturers, four questionnaires from the Institution, and five questionnaires from industry/users of graduates were collected. The interviews were conducted with the institution. Using the nonparametric two-way chi-square test, the researcher found that the perceptions of various stakeholders regarding the need to learn English are the same, namely emphasizing the need for English after graduation (future needs). Meanwhile, immediate needs in the form of teaching programs aimed at helping students in their current studies, according to stakeholders, are the second priority. This study also found that stakeholders generally viewed the English curriculum at the Institution as good enough. It was also found that students’ perceptions of their English language skills were at odds with the perceptions of other stakeholders (English lecturers, course lecturers, Institution, and users). In the final section, a number of suggestions are given.